2016
DOI: 10.5935/1415-2762.20160018
|View full text |Cite
|
Sign up to set email alerts
|

Give Birth and Be Born in New Times: Care Provided in the Puerperium by the Hanami Team

Abstract: O objetivo deste estudo é analisar a percepção do casal sobre o processo de cuidar da Equipe Hanami no parto domiciliar planejado no puerpério. Trata-se de uma pesquisa convergente-assistencial, qualitativa, realizada com 30 casais. Os dados foram coletados durante a observação participante e a entrevista semiestruturada. A análise compreendeu as etapas do processo de apreensão, síntese, teorização e transferência, embasadas na Teoria da Diversidade e Universalidade do Cuidado Cultural e nos Modelos de Atenção… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…12 When specifically discussing puerperal return, a qualitative study verified the perception of couples about the assistance provided by the Hanami team, which makes returns at home on the 1 st , 3 rd , 7 th and 10 th days, with flexibility of returns when necessary, and more an appointment on the 30 th postpartum day. The participants reported that the assistance consisted of respectful, sensitive, competent and important care for successful breastfeeding, 24 giving importance to the consultation, more frequent evaluation, and in critical moments of the puerperium.…”
Section: Coefficientmentioning
confidence: 99%
“…12 When specifically discussing puerperal return, a qualitative study verified the perception of couples about the assistance provided by the Hanami team, which makes returns at home on the 1 st , 3 rd , 7 th and 10 th days, with flexibility of returns when necessary, and more an appointment on the 30 th postpartum day. The participants reported that the assistance consisted of respectful, sensitive, competent and important care for successful breastfeeding, 24 giving importance to the consultation, more frequent evaluation, and in critical moments of the puerperium.…”
Section: Coefficientmentioning
confidence: 99%